Determination of concrete strength and toughness from notched 3 PB specimens of same depth but various span-depth ratios. (15th March 2021) - Han, Xiangyu; Chen, Yi; Xiao, Qinghua; Cui, Kai; Chen, Qiaofeng; Li, Congming; Qiu, Zemin
Highlights: The Y(α) of various 3-p-b specimens is calculated by linear interpolation method. The influence of span/depth ratios is incorporated into the equivalent crack length. The proposed fracture analysis method is verified by the published data. The specimen weight should be considered when the span/depth is greater than 4.0. Abstract: Notched three-point-bending (3 PB) tests of small concrete samples with a fixed depth/size but various span/depth ratios can be performed in almost every laboratory. Additional usefulness is added to the flexibility of those fixed-depth 3 PB tests in this study by providing a simple closed-form solution for determination of the depth and span independent tensile strength ft and fracture toughness KIC measurable from 3 PB samples with any span-depth ratio. Material constants, ft and KIC, only existed asymptotically for large concrete structures are determined by the simple fracture mechanics model regardless the span-depth ratio. Recent results of notched 3 PB tests with 6 span-depth ratios (2, 2.5, 3, 4, 5 and 6) were analysed again by the closed-form model and compared with the effective fracture toughness in the previous study (without ft ). A good agreement in KIC values was obtained. That is the two different fracture models have affirmed the usefulness of small notched 3 PB tests of a fixed depth/size but with flexible choices of the span/depth ratio. Moreover, the weight of specimens is suggested to be considered when the span/depth ratio is greater than 4.0 for 3 PB tests. Finally, fracture statistics analysis, not considered by the previous method, was included in this study, which provided the 95% reliability band besides the mean ft and KIC values.